PENERAPAN ASSESSMEN KINERJA BERBASIS POBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Himsar Himsar; Sri Amila (Institut Agama Islam Negeri Padangsidimpuan, 2023)
The learning process through careful planning and integrated with thinking power will lead students to become whole attitudes, knowledge, skills and critical thinking. . The application of problem-based learning-based performance assessment is one of the efforts to regenerate the competence integrity of students. students whose attitudes, knowledge and skills are intact will produce good critical thinking skills. This study uses PTK (Classroom Action Research) which consists of 2 cycles. Prior to conducting the research, an initial test was carried out with an average class score of 68 attitudes, 67.5 knowledge, 65 skills and 60 critical thinking, meaning that all aspects were still below the KKM (Minimum Completeness Criteria) 70. Researchers conducted learning using the PBL model in cycles I and II. The average value of the first cycle class is attitude 75, knowledge 78, skills 76 and critical thinking 68, meaning that each student's value is above KKM 70 except for critical thinking aspects. Cycle II students obtained better scores than pre-research and cycle I, namely the average value of attitude class was 86.8, the value of knowledge was 88.6, the value of skills was 85.8 and critical thinking was 75, meaning that all class scores were above the KKM. The results of this study can improve the learning process that is declining and foster students' performance processes, cooperative attitudes, eliminate selfish attitudes and improve students' critical thinking skills.